Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.

Synthesis of a 3D free standing crystalline NiSex matrix for electrochemical energy storage applications - Dinara, Syed Mukulika; Samantara, Aneeya K.; Das, Jiban K.; Behera, J. N.; Nayak, Saroj K.; Late, Dattatray J.; Rout, Chandra Sekhar (Dalton Transactions, 2019)
The electrochemical performance for energy storage of three-dimensional (3D) self-supported heterogeneous NiSex cubic-orthorhombic nanocrystals grown by a facile one-step chemical vapour deposition (CVD) approach on Ni foam substrates has been explored. NiSex shows a high specific capacitance of 1333 F g(-1) with ultra-high energy (105 W h kg(-1)) and power (54 kW kg(-1)) densities. Furthermore, by integrating the as-grown NiSex as the anode and reduced graphene oxide as the cathode, a hybrid super-capacitor (HSC) prototype with a coin cell configuration has been fabricated. The device shows better capacitance (40 F g(-1)) with high energy (22 W h kg(-1)) and power (5.8 kW kg(-1)) densities and robust cycling durability (similar to 88% capacitance retention after 10 000 repeated cycles). For practical reliability of the as-fabricated HSC, a red LED has been illuminated by connecting it with two charged coin cells. These outstanding performances of the HSC prove to be promising for applications in high energy storage systems.